Improved DTC-SVM Based on Input-Output Feedback Linearization Technique Applied on DOEWIM Powered by Two Dual Indirect Matrix Converters - Mourad Sellah (Energies, 2021)
This paper focuses on the application of the direct torque control based on space vector modulation (DTC-SVM), combined with the input–output feedback linearization (IOFL) technique on a three-phase dual open-end windings induction motor (DOEWIM) fed by two dual indirect matrix converters. The main aim of integrating the non-linear technique is to overcome the main drawbacks met within the application of the conventional DTC-SVM on dual-stator induction motor (DSIM), such as the torque and flux ripples reduction, the stator harmonics current minimization, and the elimination of the common-mode voltage (CMV). Furthermore, it is proved in this paper that the proposed control on DOEWIN can ensure more flexibility versus speed reverse and variation, load torque changes, and motor parameters variation. The obtained results prove the validity of the proposed control on the studied induction motor topology in ensuring the main aforementioned advantages compared to the conventional DTC-SVM control on DSIM, which presents a promising solution, especially in industrial applications in which high-power motors are required.